CHARACTERISTICS AND CHALLENGES OF THE IRAQI ECONOMY AFTER 2003 - Prof. Dr. Younes Boujelbene; Elham khudhair Abbas Shubbar (American Journals, 2023)
The aim of this study is to define the characteristics of the Iraqi economy that required it for a long time. The country suffered from various and successive crises until after 2003 and the subsequent years, the most important of which is the unilateralism of the economy and its dependence on oil as the sole source of its revenue and income, which constituted 90% of the total revenues and neglected the rest. The basic economic sectors such as agriculture and industry weakened their contributions to the gross domestic product and caused many institutional, economic, social and environmental challenges that impeded the development process and weakened the productive capabilities of the Iraqi economy and the diversification of its resources, We recommend adopting a serious and integrated government reform program that will help alleviate some of the problems and challenges.
Keywords: Characteristics of the Iraqi economy, economic and social challenges, institutional and environmental challenges.